Qualitive study on multicast routing protocols in manets - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana (IIUM Press, 2011)
MANETs are considered for many commercial applications, including home networks,nomadic computing, community networks and emergency response networks. Also, there are many applications of MANETs that involve point-to-multipoint or multipoint-to-multipoint communication patterns. Disaster recovery, search and rescue, military applications, videoconferencing or class room settings, public events, interactive television, temporary offices and multi-partiy gaming are common examples of these application [1]. As a consequence, multicast routing has received significant attention over the recent days